New Learning Technologies in Design Education - Baidabekov Әуез; Sadykova Жанна; Salykova Сауле (Рroblems of engineering and professional education, 2023)
This article is dedicated to the development of highly qualified design students. Innovative technology methods proposed for use in educational practice by design students are being studied. All methods are aimed at future professionals, their activities, interests and desire. The introduction of innovative technologies is associated with competently oriented education and projects. Particular attention should be paid to the educational process of preparing future designers for practical activity, but the theoretical basis is also important in the learning process. An example of current innovations is the idea of game methods that open up the possibility of developing students’ professional skills in design and development of competent training components. The importance of the psychological component is determined in the pedagogical process.